The discrepant severity of external and internal injuries in a traffic accident: The cushioning effect via a human body against direct impact: Autopsy cases - Nishitani, Yoko; Okazaki, Shunichiro; Suzuki, Kengo; Imabayashi, Kiyomi; Katada, Ryuichi; Matsumoto, Hiroshi (The American journal of forensic medicine and pathology, 2009)
Traffic accidents cause unexpectedly severe injuries of internal organs despite tiny injuries observed on the external body. A 51-year-old woman (subject 1) and a 54-year-old man (subject 2) were found dead on a road. Subject 1 had subcutaneous and intramuscular bleeding with décollement on the posterior aspect of her body, including upper cervical spine dislocation. Subject 2 did not exhibit any apparent findings on autopsy that were indicative of a direct injury by a motor vehicle, but had severe internal organ injuries, including the transection at the pontomedullary junction. We surmise that subjects 1 and 2 were walking in line with the vehicle which collided with them from behind, and then the body of subject 1 cushioned the direct impact of the vehicle against subject 2. This report illustrates the need of forensic autopsy for victims with no severe external injuries.